Anomalous coronary artery origin from the opposite sinus in patients with bicuspid aortic valve: comparison with tricuspid aortic valve. Issue 1 (21st June 2021) - Vallabhajosyula, Saarwaani; Fuchs, Margaret; Yang, Li-Tan; Medina Inojosa, Jose; Tajouri, Tanya H; Enriquez-Sarano, Maurice; Phillips, Sabrina D; Gulati, Rajiv; Klarich, Kyle W; Michelena, Hector
Abstract : Objective: To compare the prevalence and patterns of anomalous coronary artery origin from the opposite sinus (ACAOS) in patients with bicuspid aortic valve (BAV) and tricuspid aortic valve (TAV). Methods: Retrospective review of consecutive patients with surgically excised BAV and TAV was performed from 1994 to 2015. Clinical notes, echocardiograms, coronary angiograms, CT angiographies, and pathology reports were reviewed. ACAOS included right coronary artery from the left cusp, left circumflex artery from the right cusp and left main or left anterior descending artery from the right cusp. Results: 2371 (years 1994–2015) and 1679 (years 2009–2015) consecutive patients with pathology-confirmed BAV and TAV, respectively, and defined preoperative coronary anatomy were identified. A left dominant coronary circulation was present in 386 (18%) patients with BAV and 179 (11%) patients with TAV (p<0.001). ACAOS was identified in 43 (1.8%) patients with BAV and 15 (0.9%) patients with TAV, p=0.02. Among patients with BAV and ACAOS, the most common phenotype was right-left fusion (n=34, 79%) with present raphe (n=36, 84%), with no association between BAV phenotype and ACAOS type. On multivariate analysis, BAV status and size of the mid-ascending aorta were independently associated with ACAOS (OR 3.29; CI 1.26 to 8.6; p=0.02; OR 0.93; CI 0.87 to 0.98; p=0.01; respectively). Only two patients with ACAOS, one with BAV and one with TAV, had a perioperative coronary ischaemic event. Conclusions: The prevalence of the potentially malignant ACAOS is significantly higher (threefold higher odds) in patients with BAV as compared with TAV, yet remains uncommon in absolute terms. Most patients with BAV and ACAOS had right-left cusp fusion and present raphe. Perioperative coronary events are rare in patients with ACAOS.